2005
DOI: 10.1007/s10029-004-0312-8
|View full text |Cite
|
Sign up to set email alerts
|

Tension-free repair of hiatal hernia during laparoscopic fundoplication: a ten-year experience

Abstract: Mesh repair/patch of the esophageal hiatus can be done without infection, with results similar to standard crural repair and consistent with surgical principles of non-tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Frantzides et al used a 13×10-cm oval-shaped ePTFE mesh in large hiatal hernias (>8 cm) and reported no recurrences in their study population for a mean follow-up period of 3.3 years (range, 6 months-6 years) [7]. Similar results were exhibited by Gryska et al, who used either PTFE or composite ePTFE/ PTFE meshes in a triangular or V-formed shape [11]. The hiatoplasty was complicated with postoperative dysphagia in over 15% of their patients.…”
Section: Mesh Materialssupporting
confidence: 77%
See 2 more Smart Citations
“…Frantzides et al used a 13×10-cm oval-shaped ePTFE mesh in large hiatal hernias (>8 cm) and reported no recurrences in their study population for a mean follow-up period of 3.3 years (range, 6 months-6 years) [7]. Similar results were exhibited by Gryska et al, who used either PTFE or composite ePTFE/ PTFE meshes in a triangular or V-formed shape [11]. The hiatoplasty was complicated with postoperative dysphagia in over 15% of their patients.…”
Section: Mesh Materialssupporting
confidence: 77%
“…The range of recurrence rates of studies performing routine sutured mesh hiatoplasty ranged between 0% and 35.6%, with a median of 1.9%. Data of studies performing a tension-free hiatoplasty are scarce, with only three studies being available [4,11,24]. In these terms, a recurrence rate of 1.4% in a cumulative number of 284 patients was achieved.…”
Section: Tension-free Hiatoplastymentioning
confidence: 95%
See 1 more Smart Citation
“…Although several clinical studies with significant patient numbers [5,[19][20][21] demonstrate the safety and effectiveness of synthetic mesh reinforcement during hiatal hernia repair, a recent literature review reveals 11 articles (Table 1) describing 14 mesh-related complications. The true rate of mesh complication after cruroplasty reinforcement is unknown but series report complication rates from 1.3% [16] to 20% [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…16,24 We and others advocate the use of mesh reinforcement of hiatal hernia repair in order to decrease the hernia recurrence. 13,17,[36][37][38] The efficacy of PTFE reinforcement in hiatal herniorraphy has been demonstrated in a randomized trial. 13 Our current indication for mesh utilization is a hiatal defect greater than 5 cm.…”
Section: Discussionmentioning
confidence: 99%